Facile synthesis of AuPd/g-C3N4 nanocomposite: An effective strategy to enhance photocatalytic hydrogen evolution activity. (7th September 2017) - Han, Changcun; Gao, Yangqing; Liu, Shuang; Ge, Lei; Xiao, Nan; Dai, Dongsheng; Xu, Boran; Chen, Changfeng
Abstract: AuPd bimetallic nanoparticle (NP) modified ultra-thin graphitic carbon nitride nanosheet photocatalysts were synthesized via photochemical deposition-precipitation followed by hydrogen reduction. The crystal structure, chemical properties, and charge carrier behavior of these photocatalysts were characterized by X-ray diffraction (XRD), surface photovoltage spectroscopy (SPS), transient photovoltage spectroscopy (TPV), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), high-resolution transmission electron microscopy (HRTEM), and UV-Vis diffuse-reflectance spectroscopy (DRS). Photocatalytic H2 evolution experiments indicate that the hydrogen treated AuPd nanoparticles can effectively promote the separation efficiency of electron-hole pairs photo-excited in the g-C3 N4 photocatalyst, which consequently promotes photocatalytic H2 evolution. The 1.0 wt% AuPd/g-C3 N4 (H2 ) composite photocatalyst showed the best performance with a corresponding photocatalytic H2 evolution rate of 107 μmol h −1 . The photocatalyst can maintain most of its photocatalytic activity after four photocatalytic experiment cycles. These results demonstrate that the synergistic effect of light reduction and hydrogen reduction of AuPd and g-C3 N4 help to greatly improve the photocatalytic activity of the composite photocatalyst. Graphical abstract: Highlights: AuPd/g-C3 N4 photocatalysts were synthesized via a facile method. The AuPd/g-C3 N4 shows significantly enhanced H2 evolution activity. The intimate interfaces promote the charge transfer and separation. The mechanism was proposed and confirmed by PL and TPV results.